Оптимизация прямых показателей качества систем автоматического управления генетическими алгоритмами - Северин, Валерий Петрович; Никулина, Елена Николаевна; Тарасенко, К. А. (НТУ "ХПИ", 2013)
The problem of optimization of direct quality indexes of automatic control systems is considered. Genetic algorithms using local optimization methods are developed. Synthesis of test systems is made by direct quality indexes.
Keywords: оптимизация локальная; синтез; функции векторные целевые; модификация